Smart irrigation and soil monitoring system for taro yam cultivation / Azril Abdul Rahim, Amirul Amin Abd Halim and Roslina Mohamad - Abdul Rahim, Azril; Abd Halim, Amirul Amin; Mohamad, Roslina (2022)
The cultivation of taro yam, which began in Southeast Asia and Malaysia, has continued to expand to the present day. It is one of the crops contributing to the world's food supply and as a decorative plant. However, agricultural activities encounter issues such as a monitoring system for soil composition that is not directly integrated with the irrigation system and the inability of the irrigation system to record water usage. Hence, this research aims to develop a smart irrigation and soil monitoring system for taro yam cultivation using the internet of things. The first method to fulfill the aims is to construct the soil composition and irrigation device using NodeMcu ESP8266 to control the irrigation system autonomously. The second method consists of developing real-time monitoring systems using the Blynk 2.0 application to provide a platform for farmers to monitor the state of agricultural areas online. The following method is developing the soil composition and monitoring system operating devices and applications and experimenting with the successfully created devices. From the results, the irrigation and soil monitoring system saves around 32.5% of water usage. The usage was recorded at 3.6 litre per day before applying the irrigation and soil monitoring and was reduced to 2.43 litre per day after using the project device. In conclusion, the developed device can conveniently display the ambient air's humidity, temperature, and soil moisture conditions on smartphones and desktops. In addition, this system can maintain soil moisture according to the value of soil moisture that has been set, which can prevent excessive water use for taro yam cultivation.